Ludo Word King untuk Meningkatkan Kosakata Bahasa Inggris Siswa Sekolah Dasar - Hadiyanti, Vidya; Salim, Herli (Didaktika, 2021)
This study aims to produce a product in the form of ludo word king learning media suitable for use in learning English vocabulary in grade IV SDN Gebang Raya 1. The method used is the method of Research and Development. This research is a development research which refers to the model developed by Dick and Carry, namely the ADDIE model which consists of the analysis, design, development, trial and evaluation stages. Data collection techniques in this study using interviews, and questionnaires. The results of this study were the product of Ludo Word King learning media to train the fourth-grade students' English vocabulary skills. The feasibility of the media is measured by validating the practicality and effectiveness of learning material and media. Based on the assessment obtained from the material expert validator, it got an average score of 3.5 and a percentage of 87.5%. The media expert's assessment got an average score of 3.09 and a percentage of 77.4%. Assessment of student responses got an average score of 3.59 and a percentage of 89.7%. Furthermore, from the overall assessment of material experts, media experts, and student responses, they got an average value of 3.39 and a percentage of 84.8%. It can be concluded that the assessment obtained from the overall grade of 'A' or 'Valid' with easy, clear, precise, interesting, consistent information, so that the Ludo Word King learning media does not need revision and the Ludo Word King learning media is suitable to be used to train language vocabulary skills. English as a learning medium for fourth-grade students at SDN Gebang Raya 1.